Assimetria cerebral na percepção de emoções faciais dinâmicas após acidente vascular cerebral - Lima, Eloise de Oliveira (2017)
Stroke is characterized by the sudden loss of neurological function caused by an interruption in the blood flow in the brain. Previous studies have investigated the influence of brain lesions on the recognition of facial expressions; however, the results are still contradictory about the involvement of the cerebral hemispheres in emotional processing. There are currently three theories about emotional processing. The first one, the right hemisphere hypothesis, states that this hemisphere shows superiority in the production and perception of all emotional facial expressions. The valence hypothesis defends a superiority of the left hemisphere for positive emotions and from the right hemisphere to the negative ones. The modified valence hypothesis argues that the right hemisphere is specialized for negative emotions, while both perform the processing of positive emotions. Objective: Therefore, we sought to evaluate the pattern of hemispheric dominance in the recognition of emotional facial expressions in individuals with right and left brain injury after stroke and healthy individuals by performing two experimental tasks (identification and discrimination). Method: A total of 26 participants participated in the study, eight of them with lesions in the left hemisphere (LHE), six with right hemisphere lesion (LHD) and twelve healthy participants in the control group. Each participant underwent the task of identifying dynamic facial expressions, composed of 48 stimuli, in which they should judge which face was presented among eight response options. In the task of discrimination, composed of 104 stimuli, subjects should discriminate between equal and different facial expressions. Results: The one-way ANOVA and the Bonferroni correction post hoc test showed that for the identification task the LHD group presented better performance, followed by the GC and LHE groups, with a significant difference between the LHE and GC groups (p=0,032). For the discrimination task, the best performance was related to the CG group, followed by the LHD with the LHE group, performing the lowest performance, with a significant difference between the LHE and CG groups (p=0,019). Then, the repeated measures ANOVA, with post hoc Bonferroni, showed a significant difference between groups in the recognition of four facial expressions, being the faces of pain, fear, sadness and neutral face. Conclusion: The results of this study do not support the hypothesis of the right hemisphere, valence or the modified valency hypothesis, since the GC and LHD groups identified and discriminated better than the LHE group. Studies such as this are important for measuring deficits in the recognition of emotional facial expressions in individuals after brain injury, as well as contributing to the development of post-stroke intervention and rehabilitation strategies.